2020
DOI: 10.1016/j.wem.2020.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Hematotoxic Snakebite Victim with Trauma: The Role of Guided Transfusion, Rotational Thromboelastometry, and Tranexamic Acid

Abstract: Hematotoxic snake bite is a leading cause of mortality in South India. However, it is rare for the emergency physician to encounter a patient with trauma associated with snakebite. Management of such a patient differs substantially from the routine management of either a trauma patient or a snakebite victim. A 59-y-old man was bitten by a snake, after which he lost consciousness, fell, and sustained facial trauma. He was rushed to the emergency department within 30 min and was discovered to have ongoing oromax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Discovered to have ongoing oromaxillofacial bleeding upon arrival at the emergency department. Underwent ROTEM-guided transfusion to correct coagulopathy along with mandibular repair [61].…”
Section: Abraham 2020mentioning
confidence: 99%
See 1 more Smart Citation
“…Discovered to have ongoing oromaxillofacial bleeding upon arrival at the emergency department. Underwent ROTEM-guided transfusion to correct coagulopathy along with mandibular repair [61].…”
Section: Abraham 2020mentioning
confidence: 99%
“…Overall, three ROTEM tests were conducted at one-hour increments during the treatment course until the patient had normalization of coagula-tion. The authors concluded that VETs could be effectively used in treating patients with coagulopathy secondary to envenomation [61].…”
Section: Facial Traumamentioning
confidence: 99%